Question

In Exercises 31-42, solve the initial value problem. 3(x^(2))y''-4xy'+2y=0, y(1)=2, y'(1)=1

In Exercises 31-42, solve the initial value problem.

3(x^(2))y''-4xy'+2y=0, y(1)=2, y'(1)=1

Homework Answers

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
Solve the Initial Value Problem: ?x′ = 2y−x y′ = 5x−y Initial Conditions: x(0)=2 y(0)=1
Solve the Initial Value Problem: ?x′ = 2y−x y′ = 5x−y Initial Conditions: x(0)=2 y(0)=1
For the initial value problem • Solve the initial value problem. y' = 1/2−t+2y withy(0)=1
For the initial value problem • Solve the initial value problem. y' = 1/2−t+2y withy(0)=1
Solve the initial value problem. x'=x+2y y'=7x+y with inition contitions x(0)=2 and y(0)=4.
Solve the initial value problem. x'=x+2y y'=7x+y with inition contitions x(0)=2 and y(0)=4.
Solve the following initial value problem. y''-2y'+2y=4x+5. ; y(0)=3. and y'(0)=0
Solve the following initial value problem. y''-2y'+2y=4x+5. ; y(0)=3. and y'(0)=0
Solve the initial value problem. d^2y/dx^2= -3 csc^2 x; y' (pi/4)=0; y(pi/2)=0 The solution is y=____.
Solve the initial value problem. d^2y/dx^2= -3 csc^2 x; y' (pi/4)=0; y(pi/2)=0 The solution is y=____.
Solve the initial value problem x′=x+y y′= 6x+ 2y+et, x(0) = 0, y(0) = 0.
Solve the initial value problem x′=x+y y′= 6x+ 2y+et, x(0) = 0, y(0) = 0.
(x2+2)y^'' + 4xy^' + 2y = 0 , y(0) =0 , y^'(0) = 1 Solve by...
(x2+2)y^'' + 4xy^' + 2y = 0 , y(0) =0 , y^'(0) = 1 Solve by using power series around x0= 0
For 2y' = -tan(t)(y^2-1) find general solution (solve for y(t)) and solve initial value problem y(0)...
For 2y' = -tan(t)(y^2-1) find general solution (solve for y(t)) and solve initial value problem y(0) = -1/3
Solve the initial value problem. 5d^2y/dt^2 + 5dy/dt - y = 0; y(0)=0, y'(0)=1
Solve the initial value problem. 5d^2y/dt^2 + 5dy/dt - y = 0; y(0)=0, y'(0)=1
solve the initial value problem y''-2y'+5y=u(t-2) y(0)=0 y'(0)=0
solve the initial value problem y''-2y'+5y=u(t-2) y(0)=0 y'(0)=0